2018
DOI: 10.3389/fendo.2017.00376
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Human Small Antral Follicle Development: Implications for Regulation of Ovarian Steroidogenesis and Selection of the Dominant Follicle

Abstract: Regulation of human ovarian steroidogenesis differs from other species and precise knowledge on how human small antral follicles (hSAF) develop and acquire competence for continued growth and steroid output is still incomplete. The present study has characterized almost 1,000 normal hSAF collected in connection with cryopreservation of ovarian tissue for fertility preservation. The antral follicles (ranging from 3 to 13 mm) were generally aspirated from one ovary surgically removed during the natural cycle, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
45
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 71 publications
(81 reference statements)
13
45
0
4
Order By: Relevance
“…In the primates' ovaries, the highest androgen receptor density was found in preantral and antral follicles [29], suggesting the importance of androgens in these stages of development. In humans, a recent study showed a strong association between androgen receptor and FSH receptor mRNA gene expression in antral follicles of 3-13 mm [30], supporting the existence of synergism between androgens and FSH action. Thus, according to these data, androgens are essential in early follicular phase for antral follicle growth and FSH-responsiveness and, therefore, the ovarian microenvironment characterized by higher androgens levels in patients receiving LH can contribute to a higher number of antral follicles available for recruitment under FSH stimulation in COS.…”
Section: Discussionmentioning
confidence: 90%
“…In the primates' ovaries, the highest androgen receptor density was found in preantral and antral follicles [29], suggesting the importance of androgens in these stages of development. In humans, a recent study showed a strong association between androgen receptor and FSH receptor mRNA gene expression in antral follicles of 3-13 mm [30], supporting the existence of synergism between androgens and FSH action. Thus, according to these data, androgens are essential in early follicular phase for antral follicle growth and FSH-responsiveness and, therefore, the ovarian microenvironment characterized by higher androgens levels in patients receiving LH can contribute to a higher number of antral follicles available for recruitment under FSH stimulation in COS.…”
Section: Discussionmentioning
confidence: 90%
“…По мере роста фолликула уровень ингибина А повышается постепенно, а при достижении фолликулом диаметра 13-14 мм его уровень резко повышается и концентрация превосходит концентрацию ингибина В [4]. Таким образом, уровень ингибина А значительно повышается в период резкого роста доминантного фолликула [6,44]. При этом уровень ингибина А коррелирует с уровнем эстрадиола и тестостерона [6].…”
Section: структура функции и физиологическая роль ингибинов и активиновunclassified
“…Таким образом, уровень ингибина А значительно повышается в период резкого роста доминантного фолликула [6,44]. При этом уровень ингибина А коррелирует с уровнем эстрадиола и тестостерона [6]. Формирование желтого тела указывает на конец фолликулярного цикла, и если происходит [4].…”
Section: структура функции и физиологическая роль ингибинов и активиновunclassified
See 2 more Smart Citations